The Influence of Duolingo Gamification in Teaching EFL of The Eight Grade Students of SMPN 8 Parepare - Usrul Bin Sani (Pusat Pengembangan Publikasi dan Hak Kekayaan Intelektual Universitas Muhammadiyah Parepare, 2020)
This research explores the idea of using an already existing language learning app, Duolingo, to students at SMPN 8 parepare. These types of apps use adaptive learning technologies, which are able to tailor the tasks to the level of each student. In the case of this research, Duolingo was used as part of the media of studies in teaching EFL. The students used the app online, either in its android phone or IOS phone. The purpose of this research is to find out the use of Duolingo Gamification is able to influence the EFL students in learning EFL or not and to analyze the significant difference between the EFL learner’s mastery in English language before and after being taught by using Duolingo Gamification. The researcher applied quasi-experimental method, with two group pre-test and post-test design. The samples of this research consisted of 42 students from two classes taken from the population of the eight grade students of SMPN 8 Parepare. Preliminary results shows that Duolingo Gamification is an easy-to-use app that is useful and has potential, although its main lessons are not based on communicative competence. It is enjoy learning process and can motivate the students because of several elements, such as the accessibility on a mobile device, its Gamification aspect, and the variety of tasks. The results of data analysis showed that there was significant difference between the EFL learner mastery in English language before and after being taught by using Duolingo Gamification. This is indicated by the mean score of the pre-test is 35.85 and the post-test is 66.42. The results of the data show the t-test value in the post-test is 5.751 and the t-table value is 2.021. The data shows that H1 is accepted and H0 is rejected and students who are taught through Gamification Duolingo media are better than students who are taught through the Picture media.